Reconstruction of Legal Protection for Victims of Crime from a Victimology Perspective in Indonesia - Resi Bumi; Kuat Puji Prayitno; Dwi Hapsari Retnaningrum (International Journal of Social Science and Religion (IJSSR), 2026)
The legal protection of victims of crime requires serious attention, as the victims frequently refuse to respect their human rights. In the criminal justice system in Idonesia the rights of victims of criminal acts are not widely accommodated, as the normative provision in the Act only states that the victim of a serious offence can obtain compensation from the state. With regard to criminal acts, it should be recognised that not all perpetrators can pay damages or compensation. So in this case, the state must play a role in restoring the condition of victims of crime, which can undermine the dignity and dignity of the victims